Do Digitalisation and Entrepreneurship Influence Export Diversification in Oil-Exporting MENA Countries? A Panel Data Analysis - Besma KIHAL (Management and Economics Review)
This research uses panel data analysis to examine the impact of digitalisation and entrepreneurship on the diversification of non-oil exports in 11 oil-exporting MENA countries, including Algeria, Saudi Arabia, Egypt, Qatar and the UAE, from 2009 to 2022. Using a Generalised Least Squares (GLS) model, the findings reveal that digitalisation positively influences export diversification, while entrepreneurship and oil rent have a significantly negative effect. The study aims to provide policymakers with recommendations to better leverage these factors and promote sustainable economic growth through diversified exports.